Controle biológico de fitonematóides mediante aplicação de fungos nematófago e micorrízicos na cultura da soja - Messa, Vinícius Rigueiro (2020)
Root-Knot nematodes (Meloidogyne spp.) are among the main phytopathogens of the root system, limiting production in the infested areas, which is favored due to the wide range of hosts. The chemical control of this is based on the use of synthetic nematicides that have high toxicity, but with low durability, requiring the development of alternative methods with a broad spectrum. A new control alternative for phytonmatoids needs to be found in order to optimize the sustainable management of crops. Given the above, this dissertation aimed to evaluate the effect of the Purpureocillium lilacinum isolate, and of the arbuscular mycorrhizal fungi (AMF) Claroideoglomus etunicatum and Rhizophagus clarus as a biocontrol agent and resistance inducer of Meloidogyne incognita. For this, an experiment was carried out with the soybean culture in a greenhouse, evaluating nematological, mycorrhizal and vegetative variables. The experimental design used was completely randomized with six different formulations of fungal isolates with five replicates each. The commercial standard nematophagous fungus P. lilacinum (Simbiose®) was applied in liquid suspension and the endomycorrhizal fungi from the International Culture Glomeromycota Collection (CICG) applied to inoculum soil. The isolates were placed under the seed in order to simulate the furrow application. Soybean cv. Monsoy 6410 IPRO, susceptible to M. incognita was used. The sowing of two seeds was carried out in 2 L plastic pots with a mixture of sand and soil in the proportion of 3: 1 (sand: soil). The inoculation of 2000 eggs and eventual (J2) per plant was carried out in sequence. The variables were evaluated 65 days after inoculation. The data were subjected to a means comparison test at 5% probability of error. The nematophagous fungus P. lilacinum confirmed its high potential in the control of M. incognita, exerting strong pressure on the reproductive capacity of the pathogen, which presented 89% and 74% reduction in the number of eggs + J2 in the soybean roots and in the soil respectively, which can act as a complementary strategy for the control of this phytoparasite, as well as promoting plant growth. The endomycorrhizal fungus R. clarus has efficiency in attenuating the presence of the nematode in the soil and root, reducing the infectivity of the pathogen by 88% and 90% of eggs + J2 in the root and soil respectively, as well as increasing the fresh mass (MFPA). The treatment with C. etunicatum showed higher values of eggs and infectious forms of the pathogen in the root system of soybean plants, exceeding the control treatment, however, this mycorrhizal isolate in the soil was efficient with 84% reduction of eggs + J2. The interaction P. lilacinum + C. etunicatum in the root reached only 15% reduction, and in the soil, the interaction reached 41% of control, inferior in relation to the other treatments. In contrast, P. lilacinum + R. clarus reduced 87% and 89% the number of eggs + J2 in the root and soil, respectively. Therefore, there is the biocontrol potential of fungi P. lilacinum and R. clarus as a potential agricultural alternative for the biological management of M. incognita.